The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/er.5359
|View full text |Cite
|
Sign up to set email alerts
|

Structural evolution of chemically deposited binary stacks of Sb 2 S 3 ‐CuS to phase‐pure CuSbS 2 thin films and evaluation of device parameters of CuSbS 2 /CdS heterojunction

Abstract: Copper-based chalcogenide ternary compounds are promising materials to be used as absorber layer in solar cells. In this work, we have reported the preparation of copper antimony sulfide (CAS) thin films by annealing chemically deposited multi-stack of Sb 2 S 3 -CuS and the effect of thickness ratio between two binary sulfides on the formation of different crystalline phases of Cu-Sb-S system. A series of multilayer structure was prepared with different thickness of CuS in order to study the effect of copper c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The Raman spectrum of the film prepared at 350 °C, show the 127.0, 246.4, 312.7, 342.0, 468.6 cm −1 modes. The 246.4, 312.7, and 342.0 cm −1 belong to the Cu 3 SbS 4 phase, while the broad peak at 127.0, 246.4 cm −1 and the peak at 468.4 cm −1 show the film is not pure Cu 3 SbS 4 at 350 °C [40,41], which is in good agreement with the XRD results, and the common structure of Cu 3 SbS 4 was shown in figure 2(d).…”
Section: Resultsmentioning
confidence: 97%
“…The Raman spectrum of the film prepared at 350 °C, show the 127.0, 246.4, 312.7, 342.0, 468.6 cm −1 modes. The 246.4, 312.7, and 342.0 cm −1 belong to the Cu 3 SbS 4 phase, while the broad peak at 127.0, 246.4 cm −1 and the peak at 468.4 cm −1 show the film is not pure Cu 3 SbS 4 at 350 °C [40,41], which is in good agreement with the XRD results, and the common structure of Cu 3 SbS 4 was shown in figure 2(d).…”
Section: Resultsmentioning
confidence: 97%
“…The highest efficiency of CuSbS 2 thin films fabricated via electrodeposition is 3.13% (Septina et al, 2014), which is far lower than the maximum theoretical conversion efficiency of 22.9% (SLME) (Yu et al, 2013). The main factor limiting the further improvement of CuSbS 2 thinfilm solar cells are 1) rough electrodeposited metal precursors lead the thickness and composition distribution to be nonuniform (Yuan et al, 2009;Gao et al, 2020)and 2) secondary phases, such as Sb 2 S 3 , Cu 12 Sb 4 S 13 , and Cu 3 SbS 4 , easily form during annealing (Kang et al, 2018;Pal et al, 2020). Zhang et al (2016) have demonstrated the crystallinity of CuSbS 2 thin films fabricated by electrodepositing Mo/Cu/Sb metal layers followed by sulfurizing in 20% H 2 S + Ar atmosphere for 1 h at 450 °C.…”
Section: Introductionmentioning
confidence: 98%
“…CuSbS 2 is a direct bandgap material, which can be adjusted between 1.4 and 1.6 eV (Medina-Montes et al, 2018;Pal et al, 2020), and its optical absorption coefficient is greater than 10 5 cm −1 (Vinayakumar et al, 2019). Its grain growth temperature is within 300 °C-450 °C (Yang et al, 2014;Riha et al, 2017), which is lower than those of Cu (In, Ga) Se 2 and Cu 2 ZnSnS 4 .…”
Section: Introductionmentioning
confidence: 99%